How India Perceives Southeast Asia? - Pakeer Mohamed, Ahmad Shah (SUSURGALUR, 2015)
ABSTRACT: India, a country from South Asia, gained independence in 1947, after receiving Britishâs approval. Britishâs approval also meant the division of India into two large territories, that is India and Pakistan. When India emerged as a new power, it caused worry in the security aspect among the countries in the Southeast Asian region. This is mainly due to its geographical location. India is a country that has the strength and ability like that of what China has currently, and it is also the second largest country after China. India has the second largest population in the world after China, and has the potential of becoming a massively powerful country in the world. India is capable of serving power balance in Asia by facing China and Pakistan with a few evolution made in the countryâs foreign policy. At the same time, India also hopes to have a good relationship with Southeast Asia; and it is seen from its foreign policy towards Southeast Asia or more commonly known as ASEAN (Association of South East Asian Nations). The closeness of the relationship was portrayed through the enthusiasm of India to accept ASEANâs invitation to become a member of ASEAN in 1991. In the 1990s, there was an improvement in the interaction between the two parties, and firm steps were taken to integrate and cooperate in economy as well as politics and security. In fact, India also managed to provide a huge potential in developing and giving economic cooperation to ASEAN.KEY WORD: India; Foreign Policy; Bilateral; Power Balance; Good Relationship.Â IKHTISAR: âBagaimana India Melihat Asia Tenggara?â. India, sebuah negara daripada Asia Selatan, mencapai kemerdekaan pada tahun 1947 setelah mendapat persetujuan pihak British. Persetujuan British ini juga telah menandakan terpisahnya India kepada dua wilayah besar, iaitu India dan Pakistan. Kemunculan India sebagai kuasa baru telah menyebabkan kebimbangan ke atas keselamatan rantau Asia Tenggara. Ini kerana dari sudut geografi, India adalah sebuah kuasa yang memiliki kekuatan dan kemampuan sepertimana kuasa China pada hari ini. India merupakan negara kedua selepas China yang mempunyai penduduk paling ramai di dunia dan mempunyai potensi menjadi kuasa besar dunia. India dapat menyediakan keseimbangan kuasa di Asia dalam menghadapi China dan Pakistan dengan berberapa evolusi di dalam dasar luarnya. Dalam pada itu, India juga inginkan hubungan yang baik dengan Asia Tenggara dan dapat dilihat melalui dasar luar India terhadap Asia Tenggara atau lebih dikenali sebagai ASEAN. Keakraban hubungan digambarkan melalui semangat India menerima jemputan ASEAN untuk menjadi ahli ASEAN pada tahun 1991. Pada tahun 1990-an, terdapat peningkatan dalam interaksi antara kedua-dua pihak, dan langkah-langkah tegas telah diambil untuk mengintegrasikan dan bekerjasama dalam ekonomi serta politik dan keselamatan. Malah, India juga berjaya memberikan potensi besar dalam membangunkan dan memberikan kerjasama ekonomi dengan ASEAN.KATA KUNCI: India; Dasar Luar; Hubungan Dua Hala; Keseimbangan Kuasa; Hubungan Baik.About the Author: Ahmad Shah Pakeer Mohamed is a Lecturer at the Faculty of Administrative Science and Policy Studies UiTM (Technology University of MARA or Majelis Amanah Rakyat), UiTM Campus Seremban, Negeri Sembilan, Malaysia. Corresponding author is able to be contacted via phone: +6006-63422691 or e-mail: ahmadshah6767@gmail.comHow to cite this article? Pakeer Mohamed, Ahmad Shah. (2015). âHow India Perceives Southeast Asia?â in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.3(2), September, pp.169-180. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808.Chronicle of the article: Accepted (May 8, 2015); Revised (July 28, 2015); and Published (September 30, 2015).